2012
DOI: 10.1515/jbcpp-2012-0023
|View full text |Cite
|
Sign up to set email alerts
|

Study on blood glucose concentration in patients with diabetes undergoing dental extraction under local anesthesia with and without adrenaline

Abstract: Dental local anesthetic solutions containing adrenaline may safely be used in patients with diabetes who had taken their hypoglycemic medications preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Besides that there was no statistically significant difference in blood glucose levels of patients undergoing both treatments suggesting the clinical feasibility of epinephrine or felypressin administration for patients with this profile. The results of this study corroborate with Haji et al 14 and Khawaja et al 17 showing that the use of lidocaine associated to epinephrine does not present significant difference in the blood glucose alterations for compensated diabetic patients. In addition, Santos-Paul et al 18 conducted a study and demonstrated that epinephrine associated to lidocaine did not lead to hyperglycemia significant changes either in hemodynamics or in anxiety parameters in type 2 diabetic and coronary disease patients.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Besides that there was no statistically significant difference in blood glucose levels of patients undergoing both treatments suggesting the clinical feasibility of epinephrine or felypressin administration for patients with this profile. The results of this study corroborate with Haji et al 14 and Khawaja et al 17 showing that the use of lidocaine associated to epinephrine does not present significant difference in the blood glucose alterations for compensated diabetic patients. In addition, Santos-Paul et al 18 conducted a study and demonstrated that epinephrine associated to lidocaine did not lead to hyperglycemia significant changes either in hemodynamics or in anxiety parameters in type 2 diabetic and coronary disease patients.…”
Section: Resultssupporting
confidence: 91%
“…Andrade 19 states that the possible complications occurring after the administration of local anesthetics with epinephrine concentrations and volumes typically used in Dentistry are much smaller than the ones often occurring in the medical clinic. Moreover, diabetic patients have shown increased tolerance to vasoconstrictive agents and may benefit from small amounts of anesthetic solutions with epinephrine at a concentration of 1: 200,000 as long as the minimum dose employed is compatible with both deep and long enough anesthesia duration 5,14,19 . This study highlights another important factor as to values observed of oximetry and heart rate, since both parameters showed no statistically significant differences between groups, considering that diabetic patients may also present hypertension 1,3,12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that local anesthetics with adrenaline as a vasoconstrictor cause blood glucose levels to rise (2,3) . For these individuals, 3% mepivacaine without a vasoconstrictor or 3% prilocaine with 0.03 IU/mL felypressin may be advised (4,5) .…”
Section: Introductionmentioning
confidence: 99%